Temple Slaves in Antiquity: Hierodouloi / Hetairai - Leyla Aydemir (Anadolu Araştırmaları)
The status of sacred slavery, which emerged with devotion to a deity in Antiquity, brought some privileges and obligations at the same time. As temple service can change according to the deity to whom it is dedicated to, the forms of dedication that take place in different ways in various lands have caused both the social and legal status of the sacred slaves to change, as well as their duties. According to the general literature, sacred slaves sometimes accompanied priests and priestess in cult rituals, directed sacrificial ceremonies, at times took part in some tasks such as the operation of large temple lands and, the construction, and maintenance of temples, and sometimes acted as prostitutes and provided income for the temple depending on the socio-economic situation of the city where the temple was located. In this article, the conditions and criteria of all these situations will be evaluated in light of the ancient literary, epigraphic, papyrological, and modern sources by considering the terms hierodoulos and hetaira, which are used in the sense of sacred slave.